2001
DOI: 10.1046/j.0305-1846.2001.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei brucei crosses the blood–brain barrier while tight junction proteins are preserved in a rat chronic disease model

Abstract: African trypanosomiasis, sleeping sickness in humans, is caused by the systemic infection of the host by the extracellular parasite, the African trypanosome. The pathogenetic mechanisms of the severe symptoms of central nervous system involvement are still not well understood. The present study examined the routes of haematogenous spread of Trypanosoma brucei brucei (Tbb) to the brain, in particular on the question whether parasites can cross the blood-brain barrier, as well as their effect on tight junction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 24 publications
6
75
1
Order By: Relevance
“…Mice and rats show a similar outcome of T. b. brucei infection, and the penetration of parasites into the brain parenchyma occurs between 12 and 22 dpi. 26,27 It was observed that all transcripts for CXCL10, lipocalin 2, and SLPI were differentially upregulated in brains of infected rats at late stage similar to what was observed in mice ( Figure 3A-C ). Because of limitations in commercially available antibodies against rat proteins, only lipocalin 2 was analyzed in rat CSF.…”
Section: Identification Of Genes Differentially Expressed In the Braisupporting
confidence: 54%
“…Mice and rats show a similar outcome of T. b. brucei infection, and the penetration of parasites into the brain parenchyma occurs between 12 and 22 dpi. 26,27 It was observed that all transcripts for CXCL10, lipocalin 2, and SLPI were differentially upregulated in brains of infected rats at late stage similar to what was observed in mice ( Figure 3A-C ). Because of limitations in commercially available antibodies against rat proteins, only lipocalin 2 was analyzed in rat CSF.…”
Section: Identification Of Genes Differentially Expressed In the Braisupporting
confidence: 54%
“…The addition of GSH to cell cultures rescued the RNA i cell death phenotype providing further proof that GSH is an essential metabolite in these parasites. Whereas this requirement for GSH can be supplied exogenously in vitro, T. brucei is an extracellular parasite in all stages of its life cycle (42,43). Thus the parasite does not have access to the intracellular thiol pools in the host likely constraining it to supply the growth requirement for GSH through de novo synthesis.…”
Section: Induction Of ␥-Gcs Rna I Kills Trypanosomes By Depleting ␥-Gmentioning
confidence: 99%
“…In experimental animals infected with the rodent pathogenic strain T. brucei brucei, parasites appear early during infection in the choroid plexus and other circumventricular organs (2) that lack a BBB. At later stages, the parasites penetrate the BBB and enter the brain parenchyma, as revealed by double immunohistochemical labeling of parasites and brain endothelial cells in a rat model of the chronic disease (3). A larger number of parasites appear in the white matter and in the septal nuclei rather than in the cerebral neocortex.…”
Section: Introductionmentioning
confidence: 99%